Foreign experience of local government budget management: analysis and application (Journal of Economic Research & Business Administration, 2025)
Local self-government in the world is one of the most important mechanisms in solving issues of local importance and is the basis of regional development.The article explores international models of local self-government budget management and evaluates their applicability to Kazakhstan, particularly for rural development. The main research question is how foreign fiscal decentralization practices and citizen participation mechanisms can enhance local budget efficiency in Kazakhstan. Based on a comparative analysis of models from Finland, France, and Germany, the study proposes recommendations to strengthen the autonomy and financial independence of local self-governments. The research employs a qualitative methodology using comparative and systemic analysis. A limitation of the study is the absence of quantitative data and limited coverage of non-European countries.Based on the study of the experience of countries with different models of local self-government, and the work of scientists on this issue, a number of measures are proposed to improve the management of the budget of local self-government in Kazakhstan. These models are grounded in the process of establishing local self-government and the specific characteristics of how local executive authorities interact with state institutions.The  study used both dialectical, formal-logical, general and particular methods.As a result of the study, measures have been proposed to improve the budget of local self-government: the creation and strengthening of the powers of authorized bodies, the application of fiscal decentralization practices, and the improvement of the practice of increasing citizens' activity in budget management.The successful implementation of local governance reforms, informed by international best practices, necessitates the adoption of innovative mechanisms of fiscal decentralization and structured civic involvement, tailored to national contextual factors.Key words: budget, local self-government, taxes, income.